’n Nota op die aanwending van 'tradisies' in die Suid-Afrikaanse struktuuranalitiese eksegese van die Ou Testament - Lombaard, C. J. S. (Verbum et ecclesia, 1996)
In this article it is argued that the way in which the term tradition is used in the South African structural analysis of the Old Testament is in fact not true to the meaning this term had for G. von Rad. This is because the identification of traditions is not followed up with historically relating the occurrences o f a tradition to one another. The South African structural analysis cannot therefore rightly claim to add a diachronical dimension to its immanent approach by using traditions in this way.